A Retrospective Analysis on the Cystic Echinococcosis Cases Occured in Northeastern Punjab Province, Pakistan - Khan, Aisha; Zahoor, Sarmad; Ahmed, Haroon; Malik, Uzma; Bute, Rabia Amin; Muzam, Muhammad Sultanul; Simsek, Sami (Korean Soc Parasitology, Seoul Natl Univ Coll Medi, 2018)
A retrospective study was performed to report the case occurrence of cystic echinococcosis (CE) in three hospitals of north-eastern region in Punjab Province, Pakistan. We reviewed retrospectively the clinical records of patients in 4 hospitals which were diagnosed with CE during 2012-2017. A total of 198 cases, 82 (41.4%) male and 116 (58.6%) females were detected as CE. The most Highest incidence was revealed in.... 21-30 years-old group (24.2%) followed by 41-50 (22.7%), 31-40 (16.2%), 11-20 (13.6%), 51-60 (8.1%), below 10 (5.5%), over 71 (5.1%) and 61-70 year-old group (4.5%). CE was detected in various organs of infected individuals. However, most of CE cases were detected in the liver (47.4%) and lung (18.6%). The present study indicated that CE is more or less prevalent in surveyed areas and one of the most important public health problems in Punjab Province, Pakistan.
Keywords: Cystic echinococcosis; epidemiology; human; Punjab; Pakistan